Thatcherism in the 21st century : the social and cultural legacy / Antony Mullen, Stephen Farrall, David Jeffery, editors. - Mullen, Antony; Farrall, Stephen; Jeffery, David (Palgrave Macmillan, 2020)
This collection examines the social and cultural legacy of Thatcherism in the 21st century. Drawing upon perspectives from a range of disciplines, it considers how Thatcherism manifests itself today and how we can assess its long-term impact.